Students working with multiple conflicting documents on a scientific issue: Relations between epistemic cognition while reading and sourcing and argumentation in essays. (29th November 2012) - Bråten, Ivar; Ferguson, Leila E.; Strømsø, Helge I.; Anmarkrud, Øistein
<x xml:space="preserve">Abstract</x> Background There is burgeoning research within educational psychology on both epistemic cognition and multiple‐documents literacy, as well as on relationships between the two constructs. Aim To examine relationships between epistemic cognition concerning the justification of knowledge claims and sourcing and argumentation skills. Sample Participants were 51 Norwegian undergraduates. Method Three dimensions of justification were identified in think‐aloud protocols based on students' reading of six documents presenting conflicting claims on the controversial scientific issue of cell phone radiation and health risks: justification by authority, personal justification and justification by multiple sources. Hierarchical multiple regression analyses were performed to examine the unique predictability of these dimensions for essay performance after removing variance associated with prior knowledge about the topic of the documents. Results After controlling for topic knowledge, justification by multiple sources uniquely predicted students' sourcing and argumentation in essays that they wrote after reading the documents, with students trying to justify knowledge claims by corroborating across several sources of information more likely to include explicit source citations, link sources and contents, and display better, more integrated argumentation in their essays. Conclusion Findings are considered in the light of a theoretical framework for multiple‐documents literacy adapted to the domain of science, and both theoretical and educational implications are discussed.